A porphyrin-based optical sensor membrane prepared by electrostatic self-assembled technique for online detection of cadmium(II). (January 2020) - Zhao, Lizhi; Zhao, Yaxiang; Li, Rishun; Wu, Dihao; Xu, Rui; Li, Sensen; Zhang, Yuzhong; Ye, Hui; Xin, Qingping
Abstract: An optical sensor membrane was prepared by electrostatic self-assembled technique for online detection of cadmium ion (II) (Cd(II)). The optical indicator 5, 10, 15, 20-tetrakis(4-N-methylpyridyl) porphyrin p -toluenesulfonate (TMPyP) was adsorbed on a hydrolyzed polyacrylonitrile (PAN) membrane by electrostatic attraction and further immobilized through layer-by-layer deposition of poly(allylamine hydrochloride) (PAH) and poly(sodium 4-styrenesulfonate) (PSS) on the membrane surface. The electrostatic self-assembly of polyelectrolytes on the membrane is influenced by pH and salt concentration of polyelectrolytes. The optical sensor membrane shows distinct color and spectral response to Cd(II) under static and flow-through conditions based on the coordination of TMPyP with Cd(II). A faster detection of Cd(II) is achieved at higher feed concentration of Cd(II) or appropriate lower immobilization capacity of TMPyP on the membrane. The flow-through detection is also influenced by the flow rate; higher flow rate led to faster response to Cd(II) during filtration. Compared with the static process, the flow-through conditions are more conducive to faster analysis of ppb level concentration of Cd(II) (10 −3  mg L −1 ) due to a promoted mass transfer and filtration enrichment. Hence, the development of the optical sensor membrane in this study demonstrated the prospect to make membranes multifunctional with advantages for online chromatic warning in addition to adsorption/rejection of heavy metal ions in the solutions that are treated. Graphical abstract: Image 1 Highlights: An optical sensor membrane is prepared by electrostatic self-assembled technique. The optical sensor membrane responses to Cd(II) under flow-through conditions. Promoted analysis of Cd(II) at ppb level is achieved due to filtration enrichments.